Corticotropin-releasing factor neurotransmission in the lateral hypothalamus modulates the tachycardiac response during acute emotional stress in rats - Barretto-de-Souza, Lucas [UNESP] (2021)
The lateral hypothalamus (LH) is implicated in the physiological and behavioral responses during stressful events. However, the local neurochemical mechanisms related to control of stress responses by this hypothalamic area are not completely understood. Therefore, in this study we evaluated the involvement of CRFergic neurotransmission acting through the CRF1 receptor within the LH in cardiovascular responses evoked by an acute session of restraint stress in rats. For this, we investigated the effect of bilateral microinjection of different doses (0.01, 0.1 and 1 nmol/100 nL) of the selective CRF1 receptor antagonist CP376395 into the LH on arterial pressure and heart rate increases and decrease in tail skin temperature evoked by acute restraint stress. We found that all doses of the CRF1 receptor antagonist microinjected into the LH decreased the restraint-evoked tachycardia, but without affecting the arterial pressure and tail skin temperature responses. Additionally, treatment of the LH with CP376395 at the doses of 0.1 and 1 nmol/100 nL increased the basal values of both heart rate and arterial pressure, whereas the dose of 0.1 nmol/100 nL decreased the skin temperature. Taken together, these findings indicate that CRFergic neurotransmission in the LH, acting through activation of local CRF1 receptors, plays a facilitatory role in the tachycardia observed during aversive threats, but without affecting the pressor and tail skin temperature responses. Our results also provide evidence that LH CRFergic neurotransmission in involved in tonic maintenance of cardiovascular function.